Autologous Fractionated Adipose Tissue as a Natural Biomaterial and Novel One-Step Stem Cell Therapy for Repairing Articular Cartilage Defects - Li, Qi; Zhao, Fengyuan; Li, Zong; Duan, Xiaoning; Cheng, Jin; Zhang, Jiahao; Fu, Xin; Zhang, Jiying; Shao, Zhenxing; Guo, Qinwei; Hu, Xiaoqing; Ao, Yingfang (Frontiers in Cell and Developmental Biology, 2020)
Articular cartilage damage remains a tough challenge for clinicians. Stem cells have emerged promising biologics in regenerative medicine. Previous research has widely demonstrated that adipose-derived mesenchymal stem cells (ADSCs) can promote cartilage repair due to their multipotency. However, enzymatic isolation and monolayer expansion of ADSCs decrease their differentiation potential and limit their clinical application. Here, a novel adipose tissue-derived product, extracellular matrix/stromal vascular fraction gel (ECM/SVF-gel), was obtained by simple mechanical shifting and centrifugation to separate the fat oil and concentrate the effective constituents. This study aimed to evaluate the therapeutic effect of this natural biomaterial on the repair of articular cartilage defects. Scanning electron microscopy showed that the fibrous structure in the ECM/SVF-gel was preserved. ADSCs sprouted from the ECM/SVF-gel were characterized by their ability of differentiation into chondrocytes, osteoblasts, and adipocytes. In a rabbit model, critical-sized cartilage defects (diameter, 4 mm; depth, 1.5 mm) were created and treated with microfracture (MF) or a combination of autologous ECM/SVF-gel injection. The knee joints were evaluated at 6 and 12 weeks through magnetic resonance imaging, macroscopic observation, histology, and immunohistochemistry. The International Cartilage Repair Society score and histological score were significantly higher in the ECM/SVF-gel group than those in the MF-treated group. The ECM/SVF-gel distinctly improved cartilage regeneration, integration with surrounding normal cartilage, and the expression of hyaline cartilage marker, type II collagen, in comparison with the MF treatment alone. Overall, the ready-to-use ECM/SVF-gel is a promising therapeutic strategy to facilitate articular cartilage regeneration. Moreover, due to the simple, time-sparing, cost-effective, enzyme-free, and minimally invasive preparation process, this gel provides a valuable alternative to stem cell-based therapy for clinical translation.